TRENDS IN THE DEVELOPMENT OF TECHNOLOGICAL COMPONENT LOGISTICS OF MSW IN POLTAVA REGION - BREDUN, Viktor (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Purpose. The aim of the study is to ensure the effectiveness of the waste management system in Poltava region for the long term of the Regional Waste Management Plan in Poltava region for 2030 (RPUV) by analyzing the prospects of the logistics organization of waste management. Methodology. This paper uses methods of factor analysis with the study of causal relationships of the impact of conceptual provisions of the regional waste management system and some organizational and technological factors of its formation, as well as methods of inductive logic in forecasting trends. Results. It is established that the main conceptual principles of development of the waste management system of Poltava region provide for the introduction of a multi-stage scheme of solid waste transportation. The compliance of the road network with the goals of the RPUV is analyzed and the main problems are identified. A detailed analysis of the quality of the road network of the region allowed to identify the roads that pose the greatest threat to the implementation of the RPUV. The main tendencies of development of the park of specialized transport equipment in different perspective periods of realization of the plan and at different stages of the organization of transportations are established. Prospects for transport support of the first stage of transportation are formulated depending on the degree of urbanization of settlements. Originality. Based on the analysis of regional features of the system of solid waste management, the most probable directions of development of the technological component of the logistics structure of the regional system of solid waste management have been identified. Practical value. The results of the study reduce the risks of the implementation of the Regional Waste Management Plan and increase the efficiency of the solid waste management system.